Differentiation Analysis of Profitability & Efficiency: Case Study at Luhve.id as MSMEs in Fashion Industry - Nurdin, Annisa Rizkitya; Akbar, Aldi (PT. Riset Press International, 2024)
This research aims to conduct a comparative analysis of the performance between MSME Luhve.id and the broader fashion industry MSME, focusing on profitability and efficiency aspects. The research method employed is quantitative descriptive analysis, with data collection through observation, interviews, and literature review. The sample utilized comprises profitability and efficiency data from Luhve.id's sales over a 36-month period from 2021 to 2023, as well as the average percentage of profitability and efficiency of the fashion industry MSME from previous studies. Data analysis techniques include normality tests and Mann-Whitney U tests. The findings reveal significant differences between MSME Luhve.id and the fashion industry in terms of profitability and efficiency. MSME Luhve.id demonstrates lower average profitability and efficiency performance compared to the fashion industry MSME. Factors influencing these differences include the relatively new age of MSME Luhve.id and the digital sales strategy that may require further development. Nonetheless, the digital strategy shows potential for long-term growth.